A Hybrid Model of Women’s Da’wah through Cultural and Digital Integration - Siti Nasikhah; Rina Antasari; Achmad Syaifudin; Rodin, Imam (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
This study examines the innovative da’wah   strategies of Muslimat Nahdlatul Ulama in integrating Ahlussunnah Wal Jama'ah (Aswaja) values amid ongoing social transformation in East OKU Regency, Indonesia. Using a field-based qualitative approach, data were collected through in-depth interviews, non-participant observations, and document analysis involving Muslimat NU leaders, religious figures, and community members. The findings indicate that Muslimat NU adopts a culturally grounded and digitally integrated da’wah   model that combines social media engagement with community-based religious activities. This approach enhances the relevance of da’wah   in contemporary society while strengthening women’s participation in both religious and social spheres. In addition, da’wah   bil-hal (action-based preaching) is implemented through socio-economic empowerment programs, enabling women to develop economic independence and active social roles. The study further reveals that Aswaja values moderation, balance, and tolerance are systematically internalized through participatory religious forums and community activities, transforming traditional gatherings into spaces for social learning and problem-solving. These strategies contribute to strengthening social cohesion and expanding the role of women as active agents in community development. This study contributes to the literature by demonstrating how local Islamic organizations adapt da’wah   practices through the integration of cultural and digital approaches to address contemporary social challenges.